Exploring the potential of starch/polycaprolactone aligned magnetic responsive scaffolds for tendon regeneration - Gonçalves, A. I. (2016)
The application of magnetic nanoparticles (MNPs) in tissue engineering (TE) approaches opens several new research possibilities in this field, enabling a new generation of multifunctional constructs for tissue regeneration. This study describes the development of sophisticated magnetic polymer scaffolds with aligned structural features aimed at applications in tendon tissue engineering (TTE). Tissue engineering magnetic scaffolds are prepared by incorporating iron oxide MNPs into a 3D structure of aligned SPCL (starch and polycaprolactone) fibers fabricated by rapid prototyping (RP) technology. The 3D architecture, composition, and magnetic properties are characterized. Furthermore, the effect of an externally applied magnetic field is investigated on the tenogenic differentiation of adipose stem cells (ASCs) cultured onto the developed magnetic scaffolds, demonstrating that ASCs undergo tenogenic differentiation synthesizing a Tenascin C and Collagen type I rich matrix under magneto-stimulation conditions. Finally, the developed magnetic scaffolds were implanted in an ectopic rat model, evidencing good biocompatibility and integration within the surrounding tissues. Together, these results suggest that the effect of the magnetic aligned scaffolds structure combined with magnetic stimulation has a significant potential to impact the field of tendon tissue engineering toward the development of more efficient regeneration therapies.